2018
DOI: 10.1089/aid.2018.0031
|View full text |Cite
|
Sign up to set email alerts
|

Weighing the Evidence of Efficacy of Oral PrEP for HIV Prevention in Women in Southern Africa

Abstract: As oral tenofovir-based regimens for preexposure prophylaxis (PrEP) are adopted as standard of care for HIV prevention, their utilization in clinical trials among women in southern Africa will require an accurate estimate of oral PrEP efficacy in this population. This information is critical for women in choosing this prevention strategy, and in public health policy making. Estimates of the efficacy of oral PrEP regimens containing tenofovir have varied widely across trials that enrolled women, with some studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 96 publications
0
17
0
Order By: Relevance
“…A series of clinical trials demonstrated that TDF/FTC can prevent HIV acquisition in MSM and women [reviewed in ].…”
Section: Discussionmentioning
confidence: 99%
“…A series of clinical trials demonstrated that TDF/FTC can prevent HIV acquisition in MSM and women [reviewed in ].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2015, trials have navigated a complex path between the evolving process of implementation and access based on in-country PrEP guidelines and decisions about study-specific access to PrEP for trial participants. [10][11][12] Ethical guidance from WHO and UNAIDS has declared that prevention trials should offer an optimised standard of prevention package, incorporating new prevention strategies as they show effectiveness and are incorporated into national policies. 13 The ECHO trial 14 was a randomised trial done to evaluate whether the risk of HIV acquisition differed substantially for women using one of three long-acting reversible contraceptives.…”
Section: Introductionmentioning
confidence: 99%
“…Nonadherence was identified as the main reason for the failure of these clinical trials. Other factors that have been identified as potential contributors to the lower efficacy of PrEP in women include socioepidemiologic characteristics (eg, transmission route, HIV subtype, exposure intensity, and percentage of population in a stable serodiscordant relationship) and biological features (eg, a difference in the distribution of ART in the female genital tract, compared with sperm or the rectum, and the peculiar composition of the vaginal microbiome) [12]. The Centers for Disease Control and Prevention therefore recommends that PrEP be taken about 20 days before vaginal sex [13].…”
Section: Analytical Treatment Interruption (Ati) Remains the Best Waymentioning
confidence: 99%